2022
DOI: 10.1002/suco.202100919
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on dynamic performance of reinforced ultra‐high ductile concrete–ultra‐high performance concrete panel under explosion

Abstract: Ultra-high ductile concrete (UHDC) is known for ultra-high tensile ductility, and ultra-high performance concrete (UHPC) has ultra-high compressive strength. Reinforced UHDC-UHPC panels that are made of UHDC and UHPC (i.e., hybrid panels) are expected to have excellent blast-resistance capacity.However, only limited research is devoted to study the dynamic performance of the panels under explosion. To further investigate the dynamic performance of such kind of composite structural system, numerical simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In recent years, members strengthened with an ECC layer have been extended to the dynamic field to satisfy the requirements of engineering structures in resisting dynamic loadings such as impact or blast. Commonly employed strengthening methods involve applying compressive or tensile strengthening to the top and bottom surfaces of the structure [64][65][66][67][68][69][70][71][72][73][74]. The fibers in the ECC layer not only improve the ductility of the layer but also increase its energy absorption capacity.…”
Section: Dynamic Performance Of Ecc Enhanced Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, members strengthened with an ECC layer have been extended to the dynamic field to satisfy the requirements of engineering structures in resisting dynamic loadings such as impact or blast. Commonly employed strengthening methods involve applying compressive or tensile strengthening to the top and bottom surfaces of the structure [64][65][66][67][68][69][70][71][72][73][74]. The fibers in the ECC layer not only improve the ductility of the layer but also increase its energy absorption capacity.…”
Section: Dynamic Performance Of Ecc Enhanced Membersmentioning
confidence: 99%
“…Moreover, for members with the same thickness of the strengthening layer, slabs strengthened on both sides performed better than those strengthened on the back side only. Liao et al [73,74] conducted experiments and simulations of strengthened ultra-high ductility concrete and ultra-high performance concrete (UHDC-UHPC) composite slabs subjected to close blast loading. Due to the ultra-high compressive strength and stiffness of the UHPC panels, there was almost no damage to the UHPC on the front side, and only multiple microcracks were observed in the UHDC on the back side under close blast loading, which indicates the excellent blast resistance of the UHDC-UHPC composite slabs.…”
Section: Dynamic Performance Of Ecc Enhanced Membersmentioning
confidence: 99%
“…In a study on the explosion resistance of upper beam and plate structures of bridges, Zhu et al 5 have studied the explosion failure mode and structural dynamic response of reinforced concrete box girders in combination with explosion tests and quantitatively evaluated the damage process of box girders subjected to vehicle explosions. Liao et al 6 studied the explosive dynamic performance of UHDC(Ultra‐high ductile concrete)–UHPC (ultra‐high‐performance concrete) panel (i.e., hybrid panel) by using numerical simulation method. It is concluded that the maximum deflection of reinforced UHDC–UHPC panels reduces with increasing scale distance and reinforcement ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the explosion‐proof effectiveness of materials should be gradually extended from the material level to the structure level to fully reveal the dynamic response characteristics, failure modes, and other changes to the protected structure after setting a protective body under the explosion impact load and to evaluate the explosion‐proof effectiveness of protective materials. At present, many scholars have used numerical simulation to explore the impact of different types of explosion‐proof materials on the explosion‐proof performance of structures under explosive impact loads and have made some theoretical achievements that are helpful in the selection and design of explosion‐proof materials 18–20 . Liu et al 21 found that the damage degree of high‐performance geopolymer composite walls reinforced by steel wire mesh (SWM) under explosive impact loads was lower than that of conventional reinforced concrete walls and SWM‐ and aluminum foam‐reinforced high‐performance geopolymer composite walls, and the integrity of the wall structure was improved, with a superior explosion‐proof effect.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many scholars have used numerical simulation to explore the impact of different types of explosion-proof materials on the explosion-proof performance of structures under explosive impact loads and have made some theoretical achievements that are helpful in the selection and design of explosion-proof materials. [18][19][20] Liu et al 21 found that the damage degree of high-performance geopolymer composite walls reinforced by steel wire mesh (SWM) under explosive impact loads was lower than that of conventional reinforced concrete walls and SWM-and aluminum foam-reinforced high-performance geopolymer composite walls, and the integrity of the wall structure was improved, with a superior explosion-proof effect. Matsagar 22 concluded that noncomposite panels composed of steel fiberreinforced concrete plates and cenospheric aluminum alloy syntactic foam composite sandwich plates offer good explosion-proof performance.…”
Section: Introductionmentioning
confidence: 99%